2003
DOI: 10.1007/s00464-002-8813-y
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after laparoscopic ventral hernia repair

Abstract: Although LVHR remains the preferred method of hernia repair at our institution, this study documents a higher recurrence rate than many other short-term series. There results underscore the importance of long-term follow-up in assessing hernia surgery outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 17 publications
4
70
1
14
Order By: Relevance
“…In addition, the overall prevalence of recurrence of 2.8% was low compared with that reported in the literature (1-20%). 5,[10][11][12][13][14] The duration of follow-up of our study was relatively short (median, 30.2 months), but most recurrences reported in the literature occur within one year of surgery, and our follow-up period is at least comparable with that of other studies. Similarly, the prevalence of recurrence reported here is equal or superior to most series of open repairs reported.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, the overall prevalence of recurrence of 2.8% was low compared with that reported in the literature (1-20%). 5,[10][11][12][13][14] The duration of follow-up of our study was relatively short (median, 30.2 months), but most recurrences reported in the literature occur within one year of surgery, and our follow-up period is at least comparable with that of other studies. Similarly, the prevalence of recurrence reported here is equal or superior to most series of open repairs reported.…”
Section: Discussionmentioning
confidence: 71%
“…La mediana del diámetro mayor de los defectos reparados fue 6 cm (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). 67,7% de los defectos reparados correspondieron a hernias incisionales, un 26% (n = 33) de los casos eran recidivas de reparaciones anteriores, esteroidales y paracetamol por horario.…”
Section: Resultsunclassified
“…La menor incidencia se ha registrado en reparaciones que utilizan puntos transfaciales y una corona doble de fijación, sobrepasando la malla 5 cm en forma circunferencial el defecto 12,13 . En nuestro caso, hemos utilizado esta técnica de fijación combinada pero con sólo una corona, lo que ha demostrado porcentaje de recidivas similares a la técnica de doble fijación 14,15 .…”
Section: Discussionunclassified
“…17 Mesh placement in the inner layer of the abdominal wall (beneath the peritoneum) seems to be the most physiological method of hernia repair, allowing the lowest relapse rate. 18 All laparoscopic hernia repair included in this study underwent the same repair technique. The mesh was positioned over the defect initially with trans-parietal stitches and then fixed to the abdominal wall with spiral tacks, even though it was suggested that tacks alone allow a higher relapse rate.…”
Section: Discussionmentioning
confidence: 99%